Tax Implication of International Accounting Standards (IAS 12) Adoption: Evidence from Deposit Money Banks (DMBS) in Nigeria - Amaechi, EGBUNIKE, Patrick; Paulinus, OKOYE, Onyii (International Journal of Social and Administrative Sciences, 2017)
The International Financial Accounting Standards (IFRSs) came into being principally to meet the information necessity of users (internal/external). In the light of this fundamental need, this study was geared towards investigating the tax implications of international accounting standards (IAS 12) adoption among selected deposit money banks (DMBs) in Nigeria. However, the expo-facto design was adopted and a sample of thirteen (13) quoted DMBs was selected for the study. The study relied solely on secondary data obtained from the annual reports and accounts of the selected DMBs. The data comprised of profit after tax, income tax, deferred tax assets and deferred tax liabilities. Consequently, the hypotheses developed were tested using mean comparison and t-test statistical tool. The study found a significant variation between the reported tax figures before and after IFRSs adoption as well as income tax rates of DMBs. In addition, findings indicated that IFRSs adoption has no significant effect on the level of profitability among the studied DMBs. On this note, the study recommended among others that standards setters and DMBs should consider the tax implication of applying any particular standard, more especially as tax laws is at variance across the globe. Furthermore, banks and accounting regulatory bodies should be trained and retrained on the application of IAS 12 standards in order to keep them abreast with recent trends on tax-related matters. As a way of doing this, the Chartered Institute of Taxation in Nigeria is advised to keep abreast with developments in IFRS and areas it may impact on the country’s tax laws; this becomes necessary especially in countries practicing common laws which Nigeria is among.